Improving public welfare through strengthening social capital and cooperative empowerment - Ni Nyoman Yuliarmi; Maryam Dunggio; I Nyoman Mahaendra Yasa (Cogent Business & Management, 2020)
A cooperative is an institution that aims to improve the welfare of its members and society. The relatively large number of cooperatives has not been able to provide a maximum contribution in improving welfare. The purpose of this research is to: 1) analyze the influence of social capital and the empowerment of cooperatives on the welfare of community members of cooperatives in Denpasar City, 2). analyzing social capital that moderates and strengthens the influence of cooperative empowerment on the welfare of cooperative members in Denpasar City. The research was conducted in the city of Denpasar, where the sample used was the members of the Multipurpose Cooperative (KSU) in Denpasar City as many as 177 people. Data analysis was performed using the SEM-PLS method. The results of data analysis conclude that social capital and the empowerment of cooperatives have a positive and significant effect on the welfare of the community who are members of cooperatives and social capital can strengthen the positive influence of cooperative empowerment on the welfare of the community in Denpasar City.
Keywords: 650; Cooperatives; public welfare; cooperative empowerment; social capital